Organizational culture, commitment, and compensation as determinants of employee retention - Muhammad Ferdiansyah; Imelda Aprileny (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study aims to investigate the effects of organizational culture, organizational commitment, and compensation on employee retention at PT PI. Employing a quantitative approach with an associative research design, the research delves into the relationships among these variables within the company context. The study's population included all employees of PT PI, and a sample was selected using a non-probability sampling method. Data were gathered through questionnaires, literature reviews, and observations to gain comprehensive insights into the factors influencing employees’ decisions to stay with the company. The findings reveal that organizational culture has a significant positive impact on employee retention. In contrast, organizational commitment did not significantly affect retention rates. Similarly, compensation also did not demonstrate a significant influence on employee retention. While compensation remains an important factor in job satisfaction, this study's results suggest it does not play a major role in employees' decisions to remain with the organization